1991
DOI: 10.1111/j.1476-5381.1991.tb12234.x
|View full text |Cite
|
Sign up to set email alerts
|

Interference of BN 52021, an antagonist of PAF, with different forms of active anaphylaxis in the guinea‐pig: importance of the booster injection

Abstract: 1 BN 52021, an antagonist of platelet activating factor (PAF), was inactive against bronchoconstriction in guinea-pigs sensitized with low amounts of ovalbumin (OA) injected twice, at a 14 day interval and challenged i.v. 7 days later. 2 Serum IgG titers increased for 7 weeks after the booster injection at day 14 and returned to low levels at day 96. 3 Administered by the intratracheal (i.t.) route at 1 mg, BN 52021 failed to inhibit bronchoconstriction induced by the i.t. administration of OA to guinea-pigs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 33 publications
(37 reference statements)
1
2
0
Order By: Relevance
“…One possible explanation for the large neutrophilic effect in our experiments involves the direct nasal instillation of the antigen. With a slightly different procedure of active sensitization, antigen challenge also caused a significant early increase in the number of eosinophils, without a change in neutrophil counts (Desquand et al, 1991). Thus, our present results support the concept that the signal for antigen-induced eosinophil and neutrophil recruitment involves different pathways, which are enhanced in sensitized guinea-pigs.…”
Section: Discussionsupporting
confidence: 84%
“…One possible explanation for the large neutrophilic effect in our experiments involves the direct nasal instillation of the antigen. With a slightly different procedure of active sensitization, antigen challenge also caused a significant early increase in the number of eosinophils, without a change in neutrophil counts (Desquand et al, 1991). Thus, our present results support the concept that the signal for antigen-induced eosinophil and neutrophil recruitment involves different pathways, which are enhanced in sensitized guinea-pigs.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, the varied responsiveness of AMs to tachykinins in vitro follows a sensitization procedure which, according to Garcez Do Carmo et al (1986), Pretolani et al (1989) and Desquand et al (1991), causes serum levels of both IgG and IgE to be significantly enhanced. AMs obtained from actively sensitized guinea-pigs have been shown to possess an impaired adenylate cyclase activity, conflicting results being reported (Bachelet et al, 1989;Beusenberg et al, 1989;.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Pretolani et al (1989) showed that BN 52021 and WEB 2086, which inhibit PAF-induced effects in isolated lungs from non-immunized or from immunized but unboosted guinea-pigs, failed to do so when the lungs are from boosted guinea-pigs. Furthermore, intratracheal administration of antigen caused a marked increase of the number of eosinophils in bronchoalveolar lavage fluids in boosted, but not in unboosted guinea-pigs (Desquand et al 1991). The efficacy of these PAF antagonists against anaphylactic bronchopulmonary responses in unboosted guinea-pigs only, suggests that the booster injection of antigen modified the lung responsiveness and PAF appears to be relevant for antigen-induced bronchopulmonary responses in unboosted animals, but loses its major role following the booster injection (Desquand et al 1991).…”
Section: Discussionmentioning
confidence: 99%